Basics of Expansion Microscopy. Issue 1 (24th October 2019) - Klimas, Aleksandra; Gallagher, Brendan; Zhao, Yongxin
Abstract: Optical imaging techniques are often used in neuroscience to understand brain function and discern disease pathogenesis. However, the optical diffraction limit precludes conventional optical imaging approaches from resolving nanoscopic structures with feature sizes smaller than 300 nm. Expansion microscopy (ExM) circumvents this limit by physically expanding preserved tissues embedded in a swellable hydrogel. Biomolecules of interest are covalently linked to a polymer matrix, which is then isotropically expanded at least 100‐fold in size in pure water after mechanical homogenization of the tissue‐gel. The sample can then be investigated with nanoscale precision using a conventional diffraction‐limited microscope. The protocol described here is a variant of ExM that uses regents and equipment found in a typical biology laboratory and has been optimized for imaging proteins in expanded brain tissues. © 2019 by John Wiley & Sons, Inc. Basic Protocol : Expansion microscopy for intact brain tissue